Effects of perioperative pelvic floor muscle training on early recovery of urinary continence and erectile function in men undergoing radical prostatectomy: a randomized clinical trial - Gislano Heverton Soares de Lira; Alexandre Fornari; Luiz Felipe Cardoso; Magda Aranchipe; Carmem Kretiska; Ernani Luis Rhoden (International Brazilian Journal of Urology, 2019)
ABSTRACT Aims: Radical prostatectomy (RP) can result in urinary incontinence (UI) and erectile dysfunction (ED), which negatively impact quality of life (QoL). This study aimed to evaluate the effects of a perioperative pelvic floor muscle training (PFMT) program versus usual care on early recovery of urinary continence and erectile function after RP. Materials and Methods: Of 59 eligible men, 31 were randomly allocated into 2 groups: Group 1 (Control, N=15) received usual post-RP care; and Group 2 (Physical therapy, N=16) received two pre-RP physical therapist-guided PFMT sessions, including exercises and electromyographic biofeedback, and verbal and written instructions to continue PFMT until RP, which was then resumed after urethral catheter removal. The International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) and the 5-item version of the International Index of Erectile Function (IIEF-5) questionnaire were used to evaluate UI and ED, respectively. Results: Demographic characteristics were similar in both groups. Three months after RP, the UI rate was 72.7% and 70.0% in Groups 1 and 2, respectively (P >0.05). The severity and frequency of UI and its impact on QoL were evaluated by the ICIQ-Short Form, with scores of 6.9±6.26 in Group 1 and 7.0±5.12 in Group 2 (P >0.05). The IIEF-5 scores were similar in Groups 1 and 2 (5.73±7.43 vs. 6.70±6.68, respectively) (P >0.05). Conclusion: Our pre-RP protocol of two physical therapist-assisted sessions of PFMT plus instructions did not significantly improve urinary continence or erectile function at 3 months after RP.